El Corregidor chileno en el siglo XVIII - Lorenzo Schiaffino, Santiago (Historia, 1999)
<span style="color: #111111; font-family: 'Trebuchet MS', 'Lucida Grande', Lucida, Verdana, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The "corregidor" in 18th-century Chile did not receive a salary, a state afffairs which required him to engage in economic activities in order to live. The result was that many of these judges engaged in trade, with an advantage over other merchants and in detriment of the execution of justice.